Cathartesaura anaerobica gen. et sp. nov., a new rebbachisaurid (Dinosauria, Sauropoda) from the Huincul Formation (Upper Cretaceous), Río Negro, Argentina - Gallina, Pablo Ariel (2005)
A new mid-sized sauropod from ‘La Buitrera’, Huincul Formation (Turonian-Coniacian), Rio Negro Province, Cathartesaura anaerobica gen. et sp. nov. is described. It is known from an incomplete, but associated skeleton that includes diagnostic postcranial elements such as a posterior cervical, an anterior caudal, and a mid caudal vertebra, a left scapula, a left ilium and a right femur. Cathartesaura anaerobica gen. et sp. nov. exhibits several autapomorphies, such as a posterior cervical vertebra with an accessory lamina that arises from the mid length of the prezygodiapophysial lamina and reaches the centrum, a thin, wing-like transverse processes on the anterior caudal vertebrae mostly supported by a ventral bony bar that frames a deep triangular fossa, and each anterior caudal neural spine with the lateral laminae composed of the spinoprezygapophyseal lamina, the lateral spinopostzygapophyseal lamina and the spinodiapophyseal lamina. The new taxon is related to Rebbachisaurus and Limaysaurus because of the presence of several synapomorphies, which support its inclusion in a separate clade of basal Diplodocoidea, the Rebbachisauridae. Aspects of rebbachisaurid vertebral anatomy including musculature and pneumaticity are briefly commented upon. A cladistic analysis is presented in an attempt to partially resolve basal diplodocoid phylogenetic relationships.